SWOT Analysis on The Views of Midwives Assigned in The Delivery Room About The Effects of The Covid-19 Pandemic: A Qualitative Study - Turfan, Esin Çeber; Özdemir, Meryem; Bidik, Nazli Unlu (Bangladesh Journal of Medical Science, 2024)
Objective: The aim of this study is to examine the experiences of midwives working in the maternity ward during the COVID-19 pandemic by SWOT analysis. Materials and Methods: A descriptive qualitative study reported following the COREQ guidelines. For the purposes of this study, 40 midwives working in the delivery room throughout the pandemic were interviewed. Research data were collected using a Personal Information Form (PIF) and a SWOT analysis interview form. One-on-one and indepth telephone interviews were conducted with the midwives. All interviews were recorded with the consent of the midwives. Collected data were transcribed and a content analysis was carried out using the MAQDA 2020 program. Results: Data collected in the study were categorized under four main themes as “Strengths”, “Weaknesses”, “Opportunities” and “Threats”. Conclusion: Midwives worked under difficult conditions during pandemi, so they were extremely tired and worn out. Midwives who could not go home during this difficult period gave psychological warfare because they were separated from their families. In addition, they thought that they could not provide adequate care and support to pregnant women at the time of delivery within the framework of social distance protection measures. This made them feel professionally inadequate. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 150-159